Pengaruh Karakteristik Good Corporate Governance Terhadap Pengungkapan Corporate Social Responsibility (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2015-2019) - Rifki Maulana; Kiagus Andi; Yenni Agustina (Universitas Malahayati, 2022)
This study aims to examine the effect of the characteristics of good corporate governance on the disclosure of corporate social responsibility studies in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. This research is motivated by the many phenomena between good corporate governance and corporate social responsibility, in wich corporate social responsibility can be implemented through regulations within the company. This analysis uses the variables of the board of commissioners, independent board of commissioners, institutional ownership, and public ownership as independent variables. The dependent variable is the disclosure of corporate social responsibility by the company. The sample in this study were 64 companies obtained from the purposive sampling method. Multiple linear regression analysis is used as a technique in tihs study. From these results it can be seen that the board of commissioners, institutional ownership, public ownership has a significant positive effect on the disclosure of corporate social responsibility of the company, while the independent board of commisssioners has no significant effect on the disclosure of corporate social responsibility of the company.Keywords: Good Corporate Governance, Corporate Social Responsibility